Strategi Humas Pemkab Boyolali Dalam Meningkatkan Citra Pemerintah Kabupaten Boyolali(Studi Deskripsi Kualitatif Media Relations Humas Pemkab Boyolali Dalam Meningkatkan Citra Pemerintah Kabupaten Boyolali) - Wartini, Wartini (2016)
Wartini, L100110040, Boyolali regency Public Relations Strategies to Improve Image Boyolali District Government (Descriptive Study of Media Relations Public Relations Boyolali regency in Improving Image Boyolali District Government), Thesis, Communication Studies, Faculty of Communication and Informatics, University of Muhammadiyah Surakarta, 2015. Boyolali district government public relations is a government agency within the village Unit (SKPD) Boyolali district. PR is an agency that presence is needed for his role in the district of Boyolali. In accordance with its role, the PR is a tool used to establish a relationship with the mass media so that the existence of a partnership. Therefore, public relations media activities relationas run as the reciprocal of the relationship with the media. This is done as to form an image within the institution. In this study will discuss how public relations strategy in enhancing the image Boyolali Regency Boyolali regency. This study aims to determine what strategies are used by public relations Boyolali regency in improving the image of Boyolali regency. This research is descriptive qualitative data collection techniques used were interviews and observation. The study concluded that public relations Boyolali district government has been running a public relations strategy: managing relationships, develop strategies and develop the network. Media relations strategy which is run by the district government public relations is the press conference, press tour, press gathering, press interviews, press releases and media pitching. Of these strategies, activities and established a harmonious relationship between them and the increased image Boyolali regency. Keywords: public relations strategy, image, Media Relations